PANDANGAN ORIENTALIS TERHADAP SEJARAH ISLAM AWAL - Rizki Ulfahadi; Reynaldi Adi Surya (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
Islamic Studies in the Western have different view and method from Eastern Islamic studies (such as Arab or Indonesia). The orientalists researched Islam through critical and historical views. One of the topics discussed in this paper is